The Learning Needs of Nursing Students in Digital Simulation Based Spiritual Care: A Qualitative Study - Dwi Setiowati; Puspita Palupi; Istahlil Adam Hussein (IQRO: Journal of Islamic Education, 2026)
Spiritual care is an essential component of holistic nursing, yet many nursing students still lack confidence in providing it. Digital simulation has emerged as an innovative strategy to address learning needs and enhance competencies in spiritual care. This exploratory qualitative study aims to explore nursing students’ learning needs regarding spiritual care through digital simulation and its contribution to the development of self-efficacy. Semi-structured in-depth interviews were conducted with 11 senior-year students (5 in clinical stages and 6 in academic stages) who had participated in digital simulations. Participants were recruited purposively until data saturation was achieved. Thematic analysis using the Braun and Clarke framework with the assistance of NVivo 12 yielded four main themes: (1) learning needs encompass spiritual assessment, empathetic communication, and cross-cultural understanding; (2) self-efficacy is still developing, reinforced by peer and faculty support; (3) digital simulations enhance self-confidence, though limited to cultural contexts; and (4) development expectations include more diverse scenarios, automated feedback, and reflective discussions with faculty. This demonstrates the potential of digital simulations in identifying learning needs and strengthening students’ spiritual care competencies. Nursing education institutions are advised to integrate them into the curriculum by strengthening faculty capacity and incorporating scenarios sensitive to cultural and religious diversity. Further quantitative research is recommended for a more objective evaluation.